Exploring authentic dodol as sustainable Malay heritage food in the southern states of Peninsular Malaysia - Ismail, Norsyahidah (2023)
The issue of food negligence and modernisation have the potential to threaten the sustainability of the traditional food existence. Reports on the issue increased and there is even an official list of endangered traditional food products in Malaysia. Dodol, despite being one of the popular traditional Malay foods in Malaysia, is listed as one of the foods. This research aimed to explore the sustainability of authentic dodol production in southern states of Peninsular Malaysia namely Melaka, Negeri Sembilan, and Johor. Accordingly, four research questions were set to understand the phenomenon in stated settings which are: 1) what is the meaning of dodol in Malay culture?, 2) what makes dodol authentic?, 3) what are the current practices in preparing dodol?, and 4) how is dodol sustained as a Malaysian heritage food? Qualitative research method was used in this study through the phenomenological case study approach. Theorized by the combination of authenticity model and sustainability theory, the primary data for this study gained from in-depth interviews with experts and consumers where data saturation point reached by the 10th informant. Participant observation, document analysis and audio-visual materials triangulate the primary data. Thematic analysis and constant comparative technique were performed using NVivo 12 software to generate themes from the data set to answer the research questions. Accordingly, the meaning of dodol in Malay culture depicted as: 1) a sweet treat served during Islamic festivals and celebrations, 2) a gourmet that symbolising prosperity, 3) a classic confectionery in the Malay heritage, and 4) a manifestation of the Malay culture. Meanwhile, the etiquettes of authentic dodol production are through: 1) the use of natural ingredients in the recipe and the traditional equipment used in the making of traditional dodol, 2) the desired original colour and its aroma, 3) the origin of the recipe (traditionally passed down from the southern states), and 4) the different types of leaves used as dodol wrappers. As the essence of the phenomenon, the structural meaning of authentic dodol current practices revealed the sustainability elements via the combinations of environmental and social through: 1) various innovations in the flavours and technology of dodol industry at present, 2) the origin of the current recipe used, 3) dodol cooking durations, and 4) preserving the traditional methods, original ingredients, tips, and skills when processing dodol. Lastly, the actual practices of the sustainability efforts were picturized by: 1) preserving the dodol-making skills in generations of family, 2) aggressive promotion of authentic dodol, 3) continuous production of authentic dodol, 4) comprehensive and integrated marketing strategies, and 5) challenges to preserve dodol. This study documented an in-depth comprehension to the phenomenon of the authentic dodol sustainability in southern states as one of the Malay traditions in food heritage. The use of authenticity within the traditional food concept were expanded with the combination of sustainability theory within this study’s heritage food context. This research provides insights to the persistence of authentic dodol that the current and future dodol entrepreneurs can benefits. Furthermore, the sustainability framework developed in this study can be used for similar subjects where authenticity is issued on its existence sustainability.